Implementation Of The Family Hope Program (PKH) In Alleviating Poverty In Sumedang Regency - Ajeng Nur Hanifah; Petrus Polyando; Dyah Poespita Ernawati (Jurnal Scientia, 2024)
Poverty is one of the problems faced by developing countries in the world, including Indonesia. The government continues to strive to address the problem of poverty through various social policies or programs, one of which is the Family Hope Program (PKH) which is regulated in Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program. The research carried out was entitled "Implementation of the Family Hope Program (PKH) in Alleviating Poverty in Sumedang Regency". This research aims to describe the implementation of the Family Hope Program (PKH) in alleviating poverty in Sumedang Regency. The theory used in this research is Edward III's implementation theory in Agustino which has 4 dimensions, namely communication, resources, disposition and bureaucratic structure. This research uses a qualitative research method with an inductive approach to be able to see the facts in the field and draw conclusions. The data sources in this research are primary data and secondary data. Data collection techniques carried out by researchers are by means of observation, interviews and documentation. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of the Family Hope Program (PKH) in overcoming poverty in Sumedang Regency has gone well, but is not optimal. The suggestion given by researchers is that the Sumedang Regency Government needs to increase cooperation with the Ministry of Social Affairs to increase the quota for PKH Facilitators. And issue a stricter policy in updating DTKS (Integrated Social Welfare Data) according to the results of validation and verification in the field so that PKH assistance can be right on target.